Development of A Thesaurus-enhanced Visual Interface for Multilingual Digital Libraries - Shiri, Ali; Ruecker, Stan; Rossello, Ximena; Bouchard, Matthew; Mehta, Paras (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The aim of this paper is to report on the development of a visual user interface enhanced with a thesaurus to support information retrieval in a multilingual digital library context. The interface provides a design to support seamless access to three spaces, namely thesaurus space, query space and result display space. Le but de cette communication est de présenter le développement d’une interface visuelle pour l’utilisateur, améliorée par un thésaurus pouvant assister le repérage d’information dans le contexte d’une bibliothèque numérique multilingue. L’interface offre une conception donnant un accès uniforme à trois espaces, à savoir l’espace thésaurus, l’espace requête et l’espace d’affichage des résultats.